AKLIMATISASI PLANLET JAHE PUTIH BESAR (Zingiber officinale) HASIL PERBANYAKAN MELALUI KULTUR IN VITRO - Ismanto, .; Djarot, Prasetyorini; Pertiwi, Anindita Aulya (Universitas Pakuan, 2024)
Giant ginger is a rhizome plant known as a spice and herbal medicine originating from South Asia, for preventing or treating various diseases because it contains gingerol. To increase the production of giant ginger plant seeds besides cultivation it can be done by utilizing in vitro culture techniques. The aim and novelty of the research is to obtain a new in-vitro medium that is suitable for producing ginger plant seeds with good and uniform quality.The research was carried out in January-December 2023. The explants used were giant ginger culture in vitro collected from the Tissue Culture Laboratory, Center for Biotechnology and Agricultural Genetic Resources. The explants were grown on MS media with the addition of a combination treatment of growth regulators BAP (0, 1, and 5 mg L-1) and TDZ (0.0, 0.1 and 0.2 mg L-1) then continued with the acclimatization process. The experimental design used was a Completely Randomized Factorial Design. The research results showed that in in-vitro the combination of 1.0 mg L-1 BAP treatment without the addition of TDZ was chosen as the ZPT concentration treatment level because it produced the best response to the growth of large white ginger explants. And in ex-vitro, the treatment combination of BAP 1.0 + TDZ 0.1, BAP 1.0 mg L-1 without the addition of TDZ, and control was chosen as the ZPT concentration treatment level because it produced the best response to the growth of giant ginger explants.